Maximizing geothermal energy utilization in the Philippines through SME Support and Intervention A Scenario Building Exercise - Rebuelta, Crispin A. Jr.; Imbang, Glen (Quezon City University of the Philippines Diliman, 2009)
Currently, United States remains the largest geothermal energy producer in the world, having 2.2 gigawatts of production capacity. This is followed by Philippines with almost 2 gigawatts of geothermal energy production. But according to Mark Taylor, a market research analyst at New Energy Finance, the Philippines could take over the lead in the next two years. The Geothermal Education Office and a 1980 article entitled "The Philippines geothermal success story" by Rudolph J. Birsic published in the journal Geothermal Energy (vol. 8, Aug.-Sept. 1980, p. 35-44) also noted the remarkable geothermal resources of the Philippines. During the World Geothermal Congress 2000 held in Beppu, Lita Prefecture of Japan (May-June 2000), it was reported that the Philippines is the largest consumer of electricity from geothermal sources and highlighted the potential role of geothermal energy in providing energy needs for the country. From an economic viewpoint, geothermal energy is extremely price competitive in some areas and reduces reliance on fossil fuels and their inherent price unpredictability. It is no secret that fuel price is one of the most volatile of all commodities. It also offers a degree of scalability : a large geothermal plant can power entire cities while smaller power plants can supply more remote sites such as rural villages. This is highly advantageous to Philippines as there are a lot of remote areas especially in provinces. However, the Philippines still has a lot of untapped of geothermal resources and it has not utilized its maximum geothermal energy resource potential. In this study, scenario building is used to develop possible scenarios for the utilization of geothermal resources in the Philippines with a particular focus on the role SMEs can play in this industry to maximize geothermal energy utilization. Using a structured methodology used in strategic management, this study will assess the current geothermal energy utilization in the Philippines and present the different factors affecting the utilization of geothermal energy both in the local and macro environment. Scenarios are then built with a focus on the role of SMEs in maximizing the utilization of geothermal energy in the country. With these scenarios, this study will present recommendations on how the utilization of geothermal energy can be maximized through SME support and intervention.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Geothermal resources -- Philippines; Business planning; Scenario building